Intestinal parasitism in the Xavánte Indians, Central Brazil - Santos, Ricardo V.; Coimbra Jr., Carlos E.A.; Flowers, Nancy M.; Silva, Joaquim P. (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
This paper reports the findings of a survey for intestinal parasites among the Xavánte Indians from Central Brazil. A. lumbricoides (25.0%) and hookworms (33.6%) were the two most common helminths; E. histolytica complex (7.8%) and G. lamblia (8.6%) the most common protozoans. The majority (58.5%) of positive individuals hosted only one species of helminth. Egg counts for helminths, and for A. lumbricoides in particular, were found to be not dispersed at random, with a few individuals, all of whom young children, showing very high counts. The prevalence rates of intestinal parasites for the Xavánte are below those reported for other Amerindian populations from Brazil.